DESIGN OF SPECIAL SERVICE TOOLS (SST) MOTORCYCLE TIMING GEAR - Abadi, Agus Haris; Buchori, Azhis Sholeh (Universitas Pendidikan Indonesia, 2021)
The purpose of designing the special service tools (SST) for motorcycle timing gear is to make it easier for mechanics to carry out the process of removing the motorcycle timing gear. The process of making this tool is carried out in several stages, including the selection of materials and the manufacturing process. The material used is S30C steel because this material has a maximum tensile strength of 48 Kg/mm. The tools used in the manufacturing process include lathes, drilling machines, grinders, saws, files, vise, hacksaws, steel rulers, pins, key sets. The measurement of the material to be used is attempted as accurately as possible in order to obtain the best results. After the required materials are available, then work on the machine tools is carried out. After this stage is complete then proceed with the finishing process. The test results show that with this tool the process of removing the timing gear on the crankshaft only takes 35.26 seconds and avoids damage to the components. The bending stress that occurs in the turning rod is still below the allowable, which is about 6.32 kg/mm. The shear stress that occurs at the hook eye is also still below the allowable, which is about 0.105 kg/mm2. The torsional stress on the pressing bolt is 0.11 kg/mm2 which is still below the allowable 4.8 kg/mm2. The root shear stress on the pressing bolt is still below the allowable, which is about 0.016 kg/mm. The root shear stress on the hook eye is still below the allowable, which is about 0.013 kg/mm. The tensile stress on the thread that occurs in the pressure bolt is still below the allowable tensile stress on the thread on the bolt, which is 0.26 Kg/mm2. The tensile stress on the thread that occurs at the hook eye is still below the allowable, which is about 0.055 kg/mm2. The tensile stress that occurs in the towing pipe is still below the allowable, which is about 0.038 kg/mm. Based on this, overall the tool is safe to use